Effect of external estradiol valerate or diethylstilbestrol on luteolysis during the luteal period in cows - Kalkan, C; Ocal, H (Scientific Technical Research Council Turkey, 1997)
The aim of this study was to determine the influence of external oestrogen hormones on initiating luteolysis. A total of 8 cows were included in the study. After the detection of first oestrus cycle, blood samples were collected 3 times a week thought the cycle. During the second oestrus cycle, animals were divided 2 groups. The first group animals received 25 mg diethylstilbestrol (DES) intra muscularly between 10(th) and 13(th) days of the cycle. The second group animals were given estradiol valerate (EV) at 5 mg/animal intra muscularly. Blood samples were collected as done during the first cycle. Progesterone levels in the blood samples were detected in a Radio Immune Assays (RIA). Average oestrus cycles in the animals given DES were 20.25+/-0.75 and 19.50+/-0.50 day before and after the DES administrations, respectively. These values were 21.25+/-1.44 day and 16.50+/-0.96 day in EV administered animals, respectively. In conclusion, a single dose DES or EV administration during the mid period of the oestrus cycle seems to effect the initiation of luteolysis in cows.
İneklerde Luteal Dönemde Uygulanan Östradiol Valerat veya Dietilstilbestrol'ün Luteolisis Üzerine Etkisi
Keywords: estradiol valerate; diethylstilbestrol; luteolysis; cow